Community and Participation in Corruption Problem Solving of Local Administrative Organizations - Rodkaew, Siraprapa; Chaiwattakul, Chidchanog; Rojanatrakul, Tanastha (Journal of Modern Learning Development, 2022)
The corruption was the problem in the community, had various stylesand had the trend higher and more complicated. The objective of this journal was to study the participation of the community in the corruption problem solving of local administrative organizations. The results found that the people should participate in the corruption problem solving of local administrative organizations in 1) knowing the information and news about the projects or activities, 2) expressing their opinion and finding the problem, the source of the problem, the need of the projects or activities, 3) considering and decision in the agreement or disagreement of the projects or activities, 4) operating in every step according the law, and 5) monitoring and evaluating the operation of the projects or activities according to the objectives and the outcome.